ENT 300 Introduction to Enterprenuership Business Proposal (Bubble Boom Enterprise) / Nor Fatin Farhana Azman...[et al.] - Sulaiman, Anis Nur Syafawani; Ismail, Maisarah; Abd Hamid, Noorfatin Adira Hazleen; Azman, Nor Fatin Farhana; Md Yusof, Noor Zaidatul Azmar; Razali, Nurul Alya Syuhada (2020)
This company located at Bandar Laguna Merbok which is near with UiTM Kedah. This is because our target market is the student there and also people around that area. We provide the affordable price for them based on their level of income. We serve the laundry service for them and vending machine that have variety of instant food and beverages from many brands.